FORMS/FORMAT 2010 Formal Methods for Automation and Safety in Railway and Automotive Systems - Schnieder, Eckehard; Tarnai, Geza.; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
Complexity in automation- and safety systems in railway as well as automotive applications are dominated more and more by formal description means, methods and tools. Formal techniques provide next to correctness and integrity checkups ? especially for safety relevant systems ? the possibility to model, prove, simulate and check the specification of the system as well as to generate the system implementations. Requirements of the CENELEC- and IEC-Standards on formal techniques, particularly with regard to the handling of safety analysis, are to be treated in FORMS/FORMAT 2010. The main focus lies on topics facing formal techniques for railway applications and intelligent transportation systems as well as for automotive applications. Gained findings, experiences and also difficulties associated with the handling of the subject matter as well as description means and tools are to be shown.
Keywords: Electronic books; Engineering; Computer simulation; Physics; System safety; Quality Control, Reliability, Safety and Risk; Automotive Engineering; Simulation and Modeling; Complexity